Asbestos exposure assessment in the first case of intrasplenic mesothelioma - Miscetti, Giorgio; Bodo, Patrizia; Lumare, A.; Abbritti, E.P.; Garofani, Patrizia; Burani, V. (La Medicina del Lavoro, 2016)
Background: In 2013 the International Journal of Surgical Pathology published a case report of intrasplenic malignant mesothelioma (MM) in a 48-year-old man: it was the first report in literature describing a case of primitive intra-splenic MM, described without  a history of asbestos exposure. Objective: To verify the possible past exposure to asbestos, ignored by the patient himself, by studying in depth his environmental and occupational history. Methods: Information about the occupational and non-occupational history of the subject was collected by Experts of the Operational Unit of Occupational Health and Safety Control (UOC PSAL) of the Local Health Unit Umbria 1 - Perugia, using the Italian National Mesothelioma Register (ReNaM) questionnaire and guide lines; an inspection was  carried out at the past canning industry where the patient worked in the period 1982-1990 and material was taken to be analysed by MOCF and SEM. Results: Samples showed the presence of asbestos  fibres belonging to the amphibole class (amosite and crocidolite) and to the serpentine class (chrysotile). Conclusions: The survey described the past occupational exposure to asbestos in a canning industry, where  the subject worked in the period 1982-1990,  unknown to the patient himself. The authors strongly confirm the  usefulness of standardized methods, such as the ReNaM Questionnaire, and the importance of technical expertise of the investigator to find and analyse the suspect materials and to demonstrate  possible past occupational exposure to asbestos.